Digital economy : emerging technologies and business innovation : third International Conference, ICDEc 2018, Brest, France, May 3-5, 2018, Proceedings /: emerging technologies and business innovation : third International Conference, ICDEc 2018, Brest, France, May 3-5, 2018, Proceedings. (2018) - Unknown
No abstract available